Fungal-derived methyldeoxaphomins target Plasmodium falciparum segregation through the inhibition of PfActin1 - Tiantian Jiang; Jin Woo Lee; Jennifer E. Collins; Samuel Schaefer; Daisy Chen; Flore Nardella; Karen Wendt; Thilini G. Peramuna; Raphaella Paes; James L. McLellan; Jasveen Bhasin; Gregory L. Durst; et al. (Proceedings of the National Academy of Sciences, 2025)
Herein we report the finding and structure determination of a natural product based on the methyldeoxaphomin scaffold family from the fungus Trichocladium asperum that shows promising antiplasmodial activity and selectivity against host cells. In vitro evolution and whole genome analysis in Plasmodium falciparum with the most potent member, NPDG-F (EC 50 of 550 nM in Dd2; 290 nM in 3D7), shows that parasite resistance to methyldeoxaphomins is strongly associated with mutations in PfActin1 (PF3D7_1246200), a critically essential ATPase needed for all stages of parasite development. Molecular docking study with available PfActin1 crystal structure shows NPDG-F occupies the same allosteric binding pocket as the known actin inhibitor cytochalasin D. The direct PfActin1 target engagement in the allosteric site was supported by cross-resistance studies, isobologram analysis with other PfActin1 inhibitors, and the structure–activity relationships for the methyldeoxaphomin family. When added to in vitro culture, NPDG-F induced morphological abnormalities in merozoite cellularization during schizogony in both the Plasmodium blood and liver stages. Our data provide chemical validation that PfActin1 is an attractive, pan-lifecycle target and inform strategies for the design of more selective inhibitors.